2000
DOI: 10.1177/147323000002800503
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase Inhibitor Ubenimex Inhibits the Growth of Leukaemic Cell Lines and Myeloma Cells through Its Cytotoxicity

Abstract: We investigated the effect of ubenimex, which has been demonstrated to have immunomodulating activities, on the proliferation of human leukaemic cell lines (HL 60 and K 562, myelogenic lines, Jurkat, a T-cell line and RPMI 8226, a multiple myeloma cell line) and on human bone marrow mononuclear cells from haematopoietic malignancy patients with acute myeloblastic leukaemia, chronic lymphocytic leukaemia or multiple myeloma. The growth of the myeloid cell lines and of a multiple myeloma cell line, but not the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Attention was drawn to the aminopeptidase family as a potential source of the CHR-2797 antiproliferative target(s) by data on the aminopeptidase inhibitors, bestatin and puromycin. These agents have been shown to exert an antiproliferative effect on a number of human tumor cell lines in vitro (10,14). When CHR-2797 was tested in aminopeptidase assays, it was found to inhibit a number of these enzymes (Table 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attention was drawn to the aminopeptidase family as a potential source of the CHR-2797 antiproliferative target(s) by data on the aminopeptidase inhibitors, bestatin and puromycin. These agents have been shown to exert an antiproliferative effect on a number of human tumor cell lines in vitro (10,14). When CHR-2797 was tested in aminopeptidase assays, it was found to inhibit a number of these enzymes (Table 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, related compounds which are poorly lipophilic are only weakly active in cell proliferation assays despite good activity against the same class of aminopeptidases, e.g., CHR-79888. The evidence that the target for these effects lay within the cell focused attention on aminopeptidases, histone deacetylases, MetAP-2, or peptide deformylase as intracellular metalloenzyme targets (2,10,(24)(25)(26). CHR-2797 has been shown to be inactive against a number of these targets (histone deacetylase, MetAP-2) and/or to affect the proliferation of a different spectrum of tumor cell lines than inhibitors of some of these targets (histone deacetylase, peptide deformylase; refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has been implicated in the control of growth and differentiation of many cellular systems. 35,36 In this study, we identified and isolated an important subpopulation of CD4 + CD25 hi Treg cells from the peripheral blood of NSCLC patients, the CD13 + CD4 + CD25 hi Fig. 1A and C).…”
Section: Introductionmentioning
confidence: 99%
“…Because of activation or malignant transformation, other leukocyte subpopulations including human B and T cells acquire significant APN gene and surface expression. Abnormal expression of "myeloid" APN on malignant lymphocytes, the activation-dependent induction of APN surface expression on tumor-infiltrating and chronic inflammatory site peripheral T cells, and the strong anti-proliferative effects of aminopeptidase inhibitors point to a linkage of APN expression and/or function to leukocyte growth (20,63). This view is supported by the observation that mutations in the gene coding for APN have been found in a number of patients suffering from leukemia and lymphoma, although these mutations are rare or absent among healthy controls (51).…”
Section: Discussionmentioning
confidence: 99%